The Transferability between L1 (Arabic) and L2 (English) Reading Comprehension - El-Ashiry, Mahmoud (2014)
Relationships between learners‟ languages were usually studied in the form of tracing transfer of linguistic items from one language to the other. This study tries to investigate the transferability of reading strategies of UAE students from the first language (Arabic) to the foreign language (English) and vice versa. The researcher tries to answer the following research questions: (1) what reading strategies are presented in first language (L1) reading textbooks and in English as foreign language (L2) reading textbooks? (2) Are there any differences in the reading strategies introduced in L1 reading textbooks and L2 reading textbooks? Based on two Cloze tests (one in Arabic and the other in English) were developed and administered to two high schools in the emirate of Fujairah, these tests were used to define good and poor readers and used as a basis for providing a reading environment in which they might use their reading strategies. In each school, and after defining good and poor achievers in the Cloze test, two subjects from each group were interviewed about the reading strategies used during the Cloze tests and if there are any strategies they transferred from L1 to L2 and vice versa. Results from the interviews indicated that good and poor readers alike transferred certain reading strategies between the two languages (Arabic and English). This study suggests there may be a far wider potential than within one country where more than one language are learned for reviewing reading strategies, implicit or intentional, in L2 textbooks and the extent to which learners are able to respond to them.